2022
DOI: 10.1002/adfm.202111077
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Role of Charged Functional Groups on Nanoparticles Grafted with Polyglycerol in Protein Adsorption and Cellular Uptake

Abstract: In biofluids, charged functional groups on the surface of nanoparticles (NPs) interact with cells through the protein corona. However, the cascade effects of charged groups on corona formation and cellular uptake remain unclear. Herein, carboxy, sulfate, and amino groups are quantitatively introduced at the periphery of polyglycerol (PG)‐grafted nanodiamond and superparamagnetic iron oxide NP to probe their roles in corona formation and cellular uptake. The uptake efficiency and intracellular aggregation state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…One probable reason for different interactions of NPs in the biological systems with multiple cell types is referred to the distinct variation in zeta potential of NPs upon exposure to cell paracrine factors. NPs with low zeta potential do not potentially interact with the cells and show a lower success of cell uptake [54,156].…”
Section: Pc Effects On Cellular Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One probable reason for different interactions of NPs in the biological systems with multiple cell types is referred to the distinct variation in zeta potential of NPs upon exposure to cell paracrine factors. NPs with low zeta potential do not potentially interact with the cells and show a lower success of cell uptake [54,156].…”
Section: Pc Effects On Cellular Interactionsmentioning
confidence: 99%
“…Also, the latter can be divided into four routes: clathrin-and caveolae-mediated endocytosis, clathrin-and caveolae-independent endocytosis, and macropinocytosis [158]. However, the presence of the PC can vary the capability of NPs to interact with cells and the corresponding cell uptake [156]. Also, it has been shown that the size, shape, and PC can change the endocytosis pathways; however they do not alter the exocytosis mechanism [159].…”
Section: Pc Effects On Cellular Interactionsmentioning
confidence: 99%
“…When x became 8, the number of carbon atoms in the main chain of Lys-aaPEA and the size of Lys-aaPEA@INS decreased with increasing y . The main cause of this phenomenon could be the stronger hydrophobic interaction; longer carbon chains improved the hydrophobicity of total Lys-aaPEA, leading to tighter structures with smaller sizes of nanocomposites. , Moreover, it was remarkable that Lys-aaPEA@INS with smaller sizes usually exhibited a higher ζ potential. In phosphate-buffered saline at pH 7.4 (PBS, pH 7.4), the polymers could form a stable nanosized suspension.…”
Section: Resultsmentioning
confidence: 99%
“…[44] Since the proteins adsorbed on the surface of NPs are well known to facilitate its recognition by mononuclear phagocyte system (MPS), the 10 B 4 C-PG in this study is supposed to be opsonized through protein adsorption. Although we reported that PG coating for NPs (NP = ND and SPION) avoids protein corona formation, [45] a much more negative zeta potential of 10 B 4 C-PG (−52 mV) than the ND-PG (around −5 mV) as shown in Figure S8, Supporting Information, is considered to induce protein attraction through electrostatic interaction, which is reported to be one of the primary forces between proteins and the NP surfaces. [44] The resulting opsonized 10 B 4 C-PG is considered to be recognized and trapped in liver and spleen.…”
Section: Pharmacokinetics Of 10 B 4 C-pgmentioning
confidence: 99%